2008
DOI: 10.1002/hep.22579
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the transcription factor recombination signal-binding protein-Jκ (RBP-J) leads to veno-occlusive disease and interfered liver regeneration in mice

Abstract: Liver sinusoid (LS) endothelial cells (LSECs) support hepatocytes in resting liversand proliferate during liver regeneration to revascularize regenerated liver parenchyma. We report that recombination signal-binding protein-J (RBP-J), the critical transcription factor mediating Notch signaling, regulates both resting and regenerating LSECs. Conditional deletion of RBP-J resulted in LSEC proliferation and a veno-occlusive disease-like phenotype in the liver, as manifested by liver congestion, deposition of fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 32 publications
1
61
0
Order By: Relevance
“…Primary murine liver sinusoid endothelial cells were isolated using a recommended protocol32 from 3 pairs of NICD ECA and control mice. MiRNA expression profiling by small RNA sequencing and data analysis were conducted by a commercial service (RiboBio).…”
Section: Methodsmentioning
confidence: 99%
“…Primary murine liver sinusoid endothelial cells were isolated using a recommended protocol32 from 3 pairs of NICD ECA and control mice. MiRNA expression profiling by small RNA sequencing and data analysis were conducted by a commercial service (RiboBio).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry analysis for CD31, vascular endothelial growth factor receptor 2, and Hif1α in tissues was performed as previously described (35). Microvessels labeled by CD31 and vascular endothelial growth factor receptor 2 (VEGFR2) were counted.…”
Section: Elisa and Immunohistochemistrymentioning
confidence: 99%
“…We report vessel enlargement or entanglement in adult uterus and gastrointestinal tract, but not in adult brain. Previous studies have shown that global deletion of Rbpj from adult mice leads to increased EC proliferation (Dou et al, 2008;Li et al, 2012;Wang et al, 2009) and vascular anomalies resembling veno-occlusive disease of the liver ) and aortic valve disease . Despite effects on the endothelium and vasculature, (not significant); N=42 controls, N=29 mutants.…”
Section: Rbpj Is Required In Postnatal Endothelium To Prevent Avmsmentioning
confidence: 99%